Dissolved trace metal speciation in estuarine and coastal waters: Comparison of WHAM/Model VII predictions with analytical results. (1st December 2014) - Stockdale, Anthony; Tipping, Edward; Lofts, Stephen
Abstract The authors apply the chemical speciation model WHAM/Model VII to investigate the distribution of metal species of Fe(III) and the divalent cations of Ni, Cu, Zn, Cd, Hg, and Pb, in the water column of estuaries and coastal areas. The authors compare, for the same locations, measured and modeled free ion and organically bound metal concentrations. The modeled free ion calculations show varying levels of agreement with experimental measurements. Where only natural organic matter is considered as the organic ligand, for Ni, Cd, and Pb, agreement within 1 order of magnitude is found in 122 of 128 comparisons. For Fe and Zn comparisons 12 of 34 (Fe) and 10 of 18 (Zn) agree to within 1 order of magnitude, the remaining modeled values being over 1 order of magnitude higher than measurements. Copper measurements agree within 1 order of magnitude of modeled values in 314 of 533 (59%) cases and are more than 1 order of magnitude lower than modeled values in 202 cases. There is a general tendency for agreement between modeled and measured values to improve with increasing total metal concentrations. There are substantial variations among different analysis techniques but no systematic bias from the model is observed across techniques. It would be beneficial to cross‐validate the different analytical methods, in combination with further modeling. The authors also assessed the effect of including an anthropogenic organic ligand (ethylenediamine tetraacetic acid (EDTA)) in the modeling, given its known presence in some coastal environments. Except for Cd, all metals were sensitive to the presence of EDTA, even at a low concentration of 50 nM. Environ Toxicol Chem 2015;34:53–63. © 2014 The Authors. Published by Wiley Periodicals, Inc. on behalf of SETAC.